2019
DOI: 10.3390/ani9100714
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Properties of Clay Minerals and Their Use as a Health Promoting Feed Additive

Abstract: Simple SummaryFeeds contaminated by mycotoxins cause organ damage, immune suppression and health disorders, limiting growth and performance of farm animals. One of the most practical approaches to minimizing the negative effect of these substances in livestock diets is by the use of different feed additives, preventing their absorption from the gastrointestinal tract. Growing interest in particular is applied to mineral additives, such as clays and clay minerals. These materials are not digested but bind toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 47 publications
0
57
0
Order By: Relevance
“…The cation exchange capacity, a number of possible charged ions by the negatively charged surface of clay materials, depends on the number of sheets and the cations located in these structures [48]. Therefore, physical and chemical properties of clay minerals depend significantly on their sheet structure, cationand anion-exchange capacity and adsorption ability which mainly determines their importance in different applications [49].…”
Section: Characteristics Of Clay Mineralsmentioning
confidence: 99%
“…The cation exchange capacity, a number of possible charged ions by the negatively charged surface of clay materials, depends on the number of sheets and the cations located in these structures [48]. Therefore, physical and chemical properties of clay minerals depend significantly on their sheet structure, cationand anion-exchange capacity and adsorption ability which mainly determines their importance in different applications [49].…”
Section: Characteristics Of Clay Mineralsmentioning
confidence: 99%
“…Kaolin clay is formed through intensive weathering of rocks rich in feldspar (granite, arkose, certain types of orthogneisses and migmatites) and it has a very high adsorbent capability. Kaolin feed additive has the ability to improve feed conversion ratio of many livestock species due to their adsorption potential of many mycotoxins [ 32 ]. Our previous findings using single adsorbents ( S. cerevisiae , kaolin and bentonite) showed that kaolin had a more reducing effect against the mold/mycotoxin induced mycotoxicosis in broilers, followed by bentonite and S. cerevisiae [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage of adsorbents is the unspecific adsorption and, hence essential nutrients might be adsorbed if their concentrations in the feed are much higher compared to those of the mycotoxin [37]. Some studies indicate that the loss of minerals can be up to 70% and must be supplemented during fattening [38][39][40]. GO is an excellent scavenger used in the detoxification of heavy metals, organic and inorganic pollutants.…”
Section: Discussionmentioning
confidence: 99%